2,3-O-(S)-Benzyl-idene-2-C-methyl-d-ribono-1,4-lactone. - Booth, K; Jenkinson, S; Fleet, G; Watkin, D (2009)
The crystal structure of the title compound, C(13)H(14)O(5), establishes (i) the (S) - rather than (R) - configuration at the acetal carbon and (ii) that both the acetal and the lactone form five- rather than six-membered rings; the absolute configuration is determined by the use of 2-C-methyl-d-ribono-1,4-lactone as the starting material. The compound consists of hydrogen-bonded chains of mol-ecules running along the a axis; there are no unusual packing features. Only classical hydrogen bonding has been considered.